IMPLEMENTASI VOICE OVER INTERNET PROTOCOL BERBASIS VPN MENGGUNAKAN METODE PPDIOO STUDI KASUS PT XYZ - Fajrin, Kurnia; Gunadi, Goldie (Infotech: Journal of Technology Information, 2024)
PT. XYZ faced communication and operational challenges between its head office and branch office employees due to limitations in using extension numbers and a company policy prohibiting the use of personal telephone numbers. In order to overcome these problems, this study used the Prepare, Plan, Design, Implement, Operate, Optimize (PPDIOO) scheme to design and implement CISCO-based VoIP technology and Virtual Private Network (VPN) based network backbone. The solution included the setup of the CISCO 2821 and the installation of CISCO IP Communicator (CIPC) software on computing devices belonging to employees in lieu of a traditional analog telephone sets. This allowed workers to call each other using the buttons from different extensions. The results showed that VPN tunneling is more optimal for delivering voice packets, and CIPC software resolved communication problems caused by damaged analog telephone sets. Implementation further discontinued the use of RJ 11 cables on each employee's desk, and employees could now take advantage of company-supplied laptops for phone use between sites. This project successfully enhanced communication and operations at PT. XYZ while adhering to company policies. ABSTRAKPT. XYZ menghadapi kendala komunikasi dan operasional antara karyawan kantor pusat dan kantor cabang akibat keterbatasan penggunaan nomor ekstensi dan kebijakan perusahaan yang melarang penggunaan nomor telepon pribadi. Untuk mengatasi kendala tersebut, penelitian ini menggunakan skema Prepare, Plan, Design, Implement, Operate, Optimize (PPDIOO) untuk merancang dan mengimplementasikan teknologi VoIP berbasis CISCO dan backbone jaringan berbasis Virtual Private Network (VPN). Solusi yang diberikan meliputi pemasangan CISCO 2821 dan pemasangan perangkat lunak CISCO IP Communicator (CIPC) pada perangkat komputasi milik karyawan sebagai pengganti telepon analog tradisional. Hal ini memungkinkan para pekerja untuk saling menelepon menggunakan tombol dari ekstensi yang berbeda. Hasil penelitian menunjukkan bahwa tunneling VPN lebih optimal untuk pengiriman paket suara, dan perangkat lunak CIPC mengatasi kendala komunikasi yang disebabkan oleh telepon analog yang rusak. Implementasi selanjutnya menghentikan penggunaan kabel RJ 11 di meja masing-masing karyawan, dan karyawan kini dapat memanfaatkan laptop yang disediakan perusahaan untuk penggunaan telepon antar lokasi. Proyek ini berhasil meningkatkan komunikasi dan operasional di PT. XYZ dengan tetap mematuhi kebijakan perusahaan.